Identification of a transporter Slr0982 involved in ethanol tolerance in cyanobacterium Synechocystis sp. PCC 6803 - Zhang, Yanan; Niu, Xiangfeng; Shi, Mengliang; Pei, Guangsheng; Zhang, Xiaoqing; Chen, Lei; Zhang, Weiwen (Frontiers in Microbiology, 2015)
Cyanobacteria have been engineered to produce ethanol through recent synthetic biology efforts. However, one major challenge to the cyanobacterial systems for high-efficiency ethanol production is their low tolerance to the ethanol toxicity. With a major goal to identify novel transporters involved in ethanol tolerance, we constructed gene knockout mutants for 58 transporter-encoding genes of Synechocystis sp. PCC 6803 and screened their tolerance change under ethanol stress. The efforts allowed discovery of a mutant of slr0982 gene encoding an ATP-binding cassette transporter which grew poorly in BG11 medium supplemented with 1.5% (v/v) ethanol when compared with the wild type, and the growth loss could be recovered by complementing slr0982 in the Δslr0982 mutant, suggesting that slr0982 is involved in ethanol tolerance in Synechocystis. To decipher the tolerance mechanism involved, a comparative metabolomic and network-based analysis of the wild type and the ethanol-sensitive Δslr0982 mutant was performed. The analysis allowed the identification of four metabolic modules related to slr0982 deletion in the Δslr0982 mutant, among which metabolites like sucrose and L-pyroglutamic acid which might be involved in ethanol tolerance, were found important for slr0982 deletion in the Δslr0982 mutant. This study reports on the first transporter related to ethanol tolerance in Synechocystis, which could be a useful target for further tolerance engineering. In addition, metabolomic and network analysis provides important findings for better understanding of the tolerance mechanism to ethanol stress in Synechocystis.